1976
DOI: 10.1037/0021-843x.85.6.543
|View full text |Cite
|
Sign up to set email alerts
|

A factor-analytic study of childhood symptoms antecedent to schizophrenia.

Abstract: A sample of child guidance clinic patients who received an adult diagnosis of schizophrenia were followed through record sources into middle adulthood. The determination of within-sample differences in long-term adult outcome provided predictive criteria. Childhood symptoms were combined into rationally derived symptom scales that were included in a IS-variable matrix. Factor analysis yielded four orthogonal factors: Unsocialized Aggressiveness, Low IQ -Poor School Achievement, Neurotic, and Schizoid. Clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 6 publications
2
10
0
1
Order By: Relevance
“…Several authors have demonstrated that premorbid behavioral, neuromotor and cognitive abnormalities precede the clinical onset of schizophrenia 20–25 . Cornblatt and Erlenmeyer‐Kimling 26 and Erlenmeyer‐Kimling et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated that premorbid behavioral, neuromotor and cognitive abnormalities precede the clinical onset of schizophrenia 20–25 . Cornblatt and Erlenmeyer‐Kimling 26 and Erlenmeyer‐Kimling et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated that premorbid behavioral, neuromotor and cognitive abnormalities precede the clinical onset of schizophrenia. [20][21][22][23][24][25] Corn- 27 suggested that, in the childhood anamnesis of adult schizophrenic patients, BA are often present and may predict the onset of the illness. Examining the premorbid development of individuals drawn from a stratified random sample of births, Jones et al 2 reported that individuals who developed schizophrenia shared delayed attainment of developmental milestones in infancy, greater social withdrawal in childhood, excessive social anxiety and poorer educational achievement in comparison with the rest of the subjects in the birth cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Independent clinical judgments Lhat were used as the basis for the consensus outcome ratings had an inlcrrater agreement of 76%. (For further information about the derivation of outcome ratings, sec Roff et al, 1976. ) Outcome ratings were significantly correlated with other indices of outcome-length of hospitalization, employment history, marital status, and level of VA compensation for psychiatric disability.…”
Section: Methodsmentioning
confidence: 99%
“…Preschizophrenic information was available from child guidance clinic records. Details of the childhood data analysis have been reported by Roff, Knight, and Wertheim (1976). This prior study found four childhood factors that were then related to a global measure of long-term adult outcome.…”
mentioning
confidence: 99%